Arzt-Bewertungsportale im Internet - Emmert, Martin; Eisenreich, Stefan; Maryschok, Markus (IMPLICONplus, 2008)

Arzt-Bewertungsportale im Internet: Eine aktuelle Bestandsaufnahme - Emmert, Martin; Sander, Uwe; Maryschok, Markus; et al. (IMPLICONplus, 2010)
WiSo-Import:2015-03-26:3404

Arzt-Bewertungsportale im Internet - Geeignet zur Identifikation guter Arztpraxen? - Emmert, Martin; Maryschok, Markus; Eisenreich, Stefan; Schöffski, Oliver (Gesundheitswesen, 2009)
WiSo-Import:2015-03-26:4434

Comparing cost-of-illness of an inpatient versus an outpatient centred treatment of patients with colorectal cancer in Bavaria, Germany from 2006 to 2008 - Emmert, Martin; Maryschok, Markus; Esslinger, Adelheid Susanne (European Journal of Public Health, 2010)
WiSo-Import:2015-03-26:4435

Informationen über die Qualität von Ärzten auf deutschen Arztbewertungsportalen - Emmert, Martin; Sander, U; Esslinger, Adelheid Susanne; Maryschok, Markus; Schöffski, Oliver (Tagungsband der eHealth2011, 2011)
WiSo-Import:2015-04-20:3410

Innovativer Einsatz von Smartphones im Gesundheitswesen - Maryschok, Markus; Schöffski, Oliver (Innovation durch Smartphone & Co. Die neuen Geschäftspotenziale mobiler Endgeräte, 2011)

Public reporting in Germany: the content of physician rating websites - Emmert, Martin; Sander, Uwe; Esslinger, Adelheid Susanne; Maryschok, Markus; Schöffski, Oliver (Methods of Information in Medicine, 2012)
<p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> Background  <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> Physician rating websites (PRWs) are gaining in popularity among patients seeking quality information about physicians. However, little knowledge is available about the quantity and type of information provided on the websites. <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> Objective <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> To determine and structure the quantity and type of information about physicians in the outpatient sector provided on German-language physician rating websites. <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> Methods  <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> In a first step, we identified PRWs through a systematic internet search using German keywords from a patient´s perspective in the two search engines Google and Yahoo. Afterwards, information about physicians available on the websites was collected and categorised according to Donabedian´s structure/process/outcome model. Furthermore, we investigated whether the information was related to the physician himself/ herself or to the practice as a whole. <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> Results  <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> In total, eight PRWs were detected. Our analysis turned up 139 different information items on eight websites; 67 are related to the structural quality, 4 to process quality, 5 to outcomes, and 63 to patient satisfaction/experience. In total, 37% of all items focus specifically on the physician and 63% on the physician’s practice. In terms of the total amount of information provided on the PRWs, results range from 61 down to 13.5 items. <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> Conclusions  <p style="margin: 0px; padding: 0px 0px 10px; color: rgb(75, 75, 77); font-family: verdana, helvetica, arial, 'frutiger linotype', 'lucida grande', sans-serif; font-size: 11px; background-color: rgb(239, 239, 240);"> A broad range of information is available on German PRWs. While structural information can give a detailed overview of the financial, technical and human resources of a practice, other outcome measures have to be interpreted with caution. Specifically, patient satisfaction results are not risk-adjusted, and thus, are not appropriate to represent a provider’s quality of care. Consequently, neither patients nor physicians should yet use the information provided to make their final decision for or against an individual physician.
Keywords: internet; Germany; patient satisfaction; information dissemination; physician rating website

Telemedizin in der akademischen Aus- und Weiterbildung am Lehrstuhl für Gesundheitsmanagement der Friedrich-Alexander-Universität Erlangen-Nürnberg - Schöffski, Oliver; Maryschok, Markus (Spektrum Telemedizin Bayern. Aktueller Überblick telemedizinscher Projekte und Anwendungen in Bayern, 2014)
Das "Spektrum Telemedizin Bayern" stellt erstmals eine große Auswahl abgeschlossener, bestehender und auch zukünftiger Projektaktivitäten im Bereich der Telemedizin in Bayern zusammen und gibt einen umfassenden Überblick zum aktuellen Entwicklungsstatus dieser Initiativen.

The German COVID-19 Digital Contact Tracing App: A Socioeconomic Evaluation - Ellmann, Stephan; Maryschok, Markus; Schöffski, Oliver; Emmert, Martin (International Journal of Environmental Research and Public Health, 2022)
The COVID-19 pandemic posed challenges to governments in terms of contact tracing. Like many other countries, Germany introduced a mobile-phone-based digital contact tracing solution (“Corona Warn App”; CWA) in June 2020. At the time of its release, however, it was hard to assess how effective such a solution would be, and a political and societal debate arose regarding its efficiency, also in light of its high costs. This study aimed to analyze the effectiveness of the CWA, considering prevented infections, hospitalizations, intensive care treatments, and deaths. In addition, its efficiency was to be assessed from a monetary point of view, and factors with a significant influence on the effectiveness and efficiency of the CWA were to be determined. Mathematical and statistical modeling was used to calculate infection cases prevented by the CWA, along with the numbers of prevented complications (hospitalizations, intensive care treatments, deaths) using publicly available CWA download numbers and incidences over time. The monetized benefits of these prevented cases were quantified and offset against the costs incurred. Sensitivity analysis was used to identify factors critically influencing these parameters. Between June 2020 and April 2022, the CWA prevented 1.41 million infections, 17,200 hospitalizations, 4600 intensive care treatments, and 7200 deaths. After offsetting costs and benefits, the CWA had a net present value of EUR 765 m in April 2022. Both the effectiveness and efficiency of the CWA are decisively and disproportionately positively influenced by the highest possible adoption rate among the population and a high rate of positive infection test results shared via the CWA.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Corona Warn App; cost–benefit analysis; COVID-19; digital contact tracing; utility analysis

Zukunftsvisionen des ambulanten Operierens am Beispiel der Kardiologie. - Leonhardt, V; Augustin, U; Maryschok, Markus; Zippel-Schulz, B; Schöffski, Oliver; Helms, TM (Ambulantes Operieren in Klinik, Praxis und MVZ. Rahmenbedingungen – Organisation – Patientenversorgung, 2016)